A COMPREHENSIVE STUDY ON THE FUTURE OF CURTAIN DESIGN PATTERNS - Ushma; Guru, Ramratan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study, "A Comprehensive Study on the Future of Curtain Design Patterns," explores the evolving trends and technological advancements shaping the curtain industry. The research highlights key findings that reveal a shift towards sustainable and smart textiles, driven by consumer demand for eco-friendly and technologically integrated home furnishings. Patterns are moving away from traditional designs to embrace more abstract, geometric, and nature-inspired motifs, reflecting broader societal trends towards minimalism and biophilia. One of the significant discoveries is the impact of digital printing technology, which allows for greater customization and intricate designs that were previously unfeasible. This advancement is expected to revolutionize the market by offering consumers bespoke options that cater to individual tastes and spatial requirements. Additionally, the study identifies a growing preference for multifunctional curtains equipped with smart features, such as light control, temperature regulation, and noise reduction, enhancing the functionality of living spaces.The research also underscores the importance of sustainability, noting a rise in the use of organic materials and recycled fabrics. This trend aligns with the global movement towards reducing environmental footprints and promotes the adoption of circular economy principles within the textile industry. In summary, the study provides a forward-looking perspective on curtain design, emphasizing the interplay between technology, aesthetics, and sustainability. The findings suggest that future curtain designs will not only serve decorative purposes but also integrate advanced functionalities, catering to the evolving needs of modern consumers. This comprehensive analysis offers valuable insights for designers, manufacturers, and retailers aiming to stay ahead in a competitive and rapidly changing market.